Organisational buyer behaviour - Naudé, Peter (Henry Stewart Talks, 2012)
Industrial marketing, B2B vs. B2C marketing, Organisational buyer behaviour, New task, modified rebuy and straight rebuy buying decisions, Three different models of organisational buyer behaviour, The work of Robinson, Faris and Wind, The work of Webster and Wind, The work of Sheth, Applications of multiple criteria decision making to organisational buyer behaviour, Different models of marketing, The work of the IMP Group, B2B marketing as the management of relationships, The ARA model (Actors, Resources and Activities), Needs, market, and transaction uncertainty, The cost of relationships, B2B marketing as a network problem, Network pictures